(3HMQ GdePgHs - (3YHO GdhGMO Hf ESeGYjd Hf CMeO, CHh GdeMGSf, aNQ GdESdGe GdQhjGfj,J (B502 (3g` s
(3ChdgG (B:s
(3cJGH GdbGVi Edi GdbGVi s
(3BNQgG (B:s
(3Gdfchd hQO Gdjejf s
(3LRA BNQ ef GdfSNI faSgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B175 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B206s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B289 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B226s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg TGaYi (B22) s
Keywords: (3Gdabg GdTGaYjs